Proportion and associated factors of respectful maternity care during childbirth in North Showa zone public health institutions, North Showa, Ethiopia: An institutional-based cross-sectional study - Amare, Nakachew Sewnet; Mekuriyaw, Abebayehu Melesew; Tesema, Getaye Worku; Ambaw, Yeshinat Lakew (Frontiers in Public Health, 2022)
Abstract Background: Respectful maternity care is one of the key strategies to increase access to use skilled maternity care services. However, limited studies are done about the extent of respectful maternity care during labor and delivery in Ethiopia, particularly in the study area. Objective: This study aimed to determine the proportion and identify the associated factors of respectful maternity care during childbirth among women who gave birth in North Showa zone public health institutions, North Showa zone, Ethiopia, 2020. Methods: An institutional-based cross-sectional study was conducted among women who got birth in North Showa public health institution from October 20 to November 20, 2020. A systematic random sampling technique was used to select study participants. Logistic regression with adjusted odds ratio and 95% uncertainty interval was used to declare statistically significant variables based on p<0.05 in the multivariable logistic regression model. Result: The overall proportion of respectful maternity care during childbirth was 48.6 % (95% CI: 44.6%-52.3%). Urban residence AOR=2.6 (95% CI: 1.8, 3.6), being multiparous AOR=1.6 (95% CI: 1.1, 2.3), having planned pregnancy AOR=2.4 (95% CI: 1.3, 4.3) and giving birth in health center AOR=1.6 (95% CI: 1.2, 2.8) were statistically significant factors with respectful maternity care during labor and delivery. Conclusions: The proportion of respectful maternity care during childbirth is low. Being from an urban community, being multiparous, having planned pregnancy, and giving birth in a health center were factors that could increase the likely hood of women getting respectful maternity care during childbirth. Based on the identified factors strategies need to be designed and implemented to enhance the level of respectful maternity care.